Netikul, T., Thawornwattana, Y., Mahasirimongkol, S., Yanai, H., Maung, H.M.W., Chongsuvivatwong, V., Palittapongarnpim, P. - Whole-genome single nucleotide variant phylogenetic analysis of Mycobacterium tuberculosis Lineage 1 in endemic regions of Asia and Africa (2023)
https://www.scopus.com/inward/record.url?eid=2-s2.0-85123875778&partnerID=40&md5=0f417df926006e16530ec99d2fde5826